Faktor-faktor yang Memengaruhi Efektivitas Sistem Informasi Akuntansi Lembaga Perkreditan Desa se-Kecamatan Tegallalang - Wahyu Kusumaningsih, Ni Wayan; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi; Vol 29 No 1 (2019)DO - 10.24843/EJA.2019.v29.i01.p14, 2019)
This study aims to determine the factors that influence the effectiveness of information systems  computer-based  by using the TAM model. This research took place at the Tegallalang District LPD. The sampling method uses purposive sampling technique. Research data was obtained through survey methods with questionnaire techniques. Analysis of research data using multiple linear regression. The results of the study are in accordance with the TAM theory that is use  namely the quality of information systems, technological sophistication and the ability of personal techniques that represent usability in TAM theory will affect personal perceptions to accept and use technology, so that it will positively affect the effectiveness of computer-based AIS. Based on the results of LPD research, it is expected to improve training in the use of accounting information systems so that the skills of employees in using the system become better so that work becomes more efficient. Keywords : TAM; Quality Of Information Systems; Technological Sophistication; Personal Technical Capabilities.